Model Manajemen Pendidikan Berbasis Masyarakat dalam Mengembangkan Lembaga Pendidikan Islam - Ruslan, Ruslan (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The development of a community-based education management model is not a separate entity from the community. However, on the contrary, Islamic educational institutions should be an integral part of society, and be able to respond to society's needs and aspirations. This research aims to analyze the community-based management model in developing Islamic educational institutions. The method used in this research is the library research method. The research results show that the community-based education management model is an approach to managing educational institutions that emphasizes the active role of the community in the decision-making process, program implementation and evaluation of educational outcomes. The application of the community-based education management model in developing Islamic educational institutions can be done through: community participation, involvement of parents in children's educational activities, integration of local and religious values ​​through learning, partnerships with local communities by involving the community in developing educational programs, curricula community-based through collaborative efforts between various educational institutions, and ongoing evaluation. It is hoped that this model can become the basis for the effective and efficient management of Islamic educational institutions, and be able to answer the challenges of an increasingly complex era.